2017
DOI: 10.1186/s13104-016-2351-5
|View full text |Cite
|
Sign up to set email alerts
|

Right iliac vein thrombosis mimicking acute appendicitis in pregnancy: a case report

Abstract: BackgroundRight iliac vein thrombosis is uncommon in pregnancy. Nonetheless, when it does occur, its presentation could be very unspecific with important diagnostic challenges and this could have negative therapeutic consequences especially in a resource limited setting.Case presentationThe historical, clinical and laboratory data of a 30 year old G2P1001 woman of African ethnicity at 11 weeks of gestation pointed towards a right iliac vein thrombosis missed for an acute appendicitis with subsequent appendecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…There are only a limited number of case reports and case series describing DVT presenting with abdominal pain in the literature. [3][4][5][6][7][8] Possible mechanisms of abdominal signs in DVT are still unclear and consist of some hypotheses in literature. Björgell et al reported that iliac DVT with phlebitis and retroperitoneal oedema might have been the cause of abdominal pain in their patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a limited number of case reports and case series describing DVT presenting with abdominal pain in the literature. [3][4][5][6][7][8] Possible mechanisms of abdominal signs in DVT are still unclear and consist of some hypotheses in literature. Björgell et al reported that iliac DVT with phlebitis and retroperitoneal oedema might have been the cause of abdominal pain in their patient.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt and accurate diagnosis is essential to avoid potential complications and unnecessary interventions. 3 We describe a case of DVT mimicking acute appendicitis in the postpartum period and heighten awareness about this rare but challenging entity.…”
Section: Introductionmentioning
confidence: 94%
“…De acordo com estudo de revisão sistemática de Chan, 71% dos casos de TVP gestacional têm envolvimento do sistema venoso proximal, sendo 64% restritos as veias ileofemorais e 17% de trombose isolada de veia ilíaca 13 . A trombose venosa pélvica pode se manifestar de uma maneira distinta e ampla, com um quadro clínico pouco frequente em mulheres não grávidas, simulando quadros de apendicite, doença inflamatória-pélvica, gravidez ectópica rota, cólica nefrética e torção de cisto ovariano 1 . As manifestações da trombose venosa proximal incluem febre, dor abdominal, dor lombar, náusea, vômitos, edema unilateral indolor e leucocitose 1 .…”
Section: Manifestações Clínicasunclassified
“…A trombose venosa pélvica pode se manifestar de uma maneira distinta e ampla, com um quadro clínico pouco frequente em mulheres não grávidas, simulando quadros de apendicite, doença inflamatória-pélvica, gravidez ectópica rota, cólica nefrética e torção de cisto ovariano 1 . As manifestações da trombose venosa proximal incluem febre, dor abdominal, dor lombar, náusea, vômitos, edema unilateral indolor e leucocitose 1 . A TVP de veias proximais possuir maior risco de embolização pulmonar (40%-50%) e resulta em maior mortalidade materna se não diagnosticada 13 .…”
Section: Manifestações Clínicasunclassified
See 1 more Smart Citation